2017
DOI: 10.3399/bjgp17x693677
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of referrals for transient ischaemic attack from first-contact health care: a systematic review

Abstract: This study highlights the variation in prevalence of true vascular events in patients referred to TIA clinics. For patients without a cerebrovascular diagnosis, the high prevalence of conditions that also require specialist investigations and management are an additional burden on a care pathway that is primarily designed to prevent recurrent stroke. Service commissioners need to assess whether the existing outpatient provision is optimal for people with pathologies other than cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Additionally, when excluding hospitalizations with stroke‐related procedures from recurrent stroke cases, the PPV for recurrent stroke increased to 78%; this increase was not statistically significant. While the PPV of 78% is a lower range of previously reported PPVs for incident stroke, it is higher than reported PPVs (12.9%–72.5%) for transient ischemic attack 14 …”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Additionally, when excluding hospitalizations with stroke‐related procedures from recurrent stroke cases, the PPV for recurrent stroke increased to 78%; this increase was not statistically significant. While the PPV of 78% is a lower range of previously reported PPVs for incident stroke, it is higher than reported PPVs (12.9%–72.5%) for transient ischemic attack 14 …”
Section: Discussioncontrasting
confidence: 78%
“…While the PPV of 78% is a lower range of previously reported PPVs for incident stroke, it is higher than reported PPVs (12.9%-72.5%) for transient ischemic attack. 14 Though the PPV of ICD-10 codes for ischemic incident stroke has been examined, 6 to date, no studies have examined the PPV of ICD-10 codes for recurrent ischemic stroke. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences between previous studies, it may be assumed that overall PPV for initially suspected stroke approaches 75% [3,7], and ranges from 13% to 73% for TIA [16]. However, if the patient is being referred from a nursing home, the PPV for stroke may be more than two-fold lower [17] In previous studies, ambulance physicians were reported to detect stroke with PPV of 67% to 83% [18].…”
Section: Discussionmentioning
confidence: 95%
“…With increasing incidence of neurological diseases, it is more likely for all doctors, especially general practitioners and internal medicine physicians, to manage neurological patients. The clinical competency of initiating primary assessment and management of neurological diseases is essential for every graduating medical student (Kandiyali et al, 2017;Bradley, 2000). The difficulty in neurology learning elicits a negative impact to medical students on both the clinical competency of dealing with neurology patients and their career choice of becoming neurologists (Pakpoor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%